miR-320b, a Future Expected New Biomarker for Type 2 Diabetes Mellitus Induces Dysglycemia by Targeting PTEN - Jinxingyi Wang; Ruyu Tao; Hanshuai Hu; Jiejie Gao; Yang Liu; Jie Xia; Xue Lan; Yanan Di (International Journal of Endocrinology)
Conclusions: Our research demonstrated a negative correlation between miR-320b and FPG, HbA1C, and HOMA-IR, while exhibiting a positive correlation with HOMA-β. Suppressing miR-320b expression would impair glucose consumption of HepG2 cells through PI3K pathway by targeting PTEN. These results suggest that miR-320b may be a potential biomarker for diagnosing T2DM and a promising target for therapeutic intervention.